Pengaruh Bermain Plastisin Terhadap Perkembangan Kreativitas Anak Di TK Negeri Satap Desa Sibargot - Nursani Rambe; Soybatul Aslamiah Ritonga; Azhar (Insan Zenius Ilmiah, 2024)
Playing with playdough is a constructive play. Creativity generates a new idea that connects with the previous one, creating something new. The problem formulation in this research is